2012
DOI: 10.2527/jas.2011-4594
|View full text |Cite
|
Sign up to set email alerts
|

MEAT SCIENCE AND MUSCLE BIOLOGY SYMPOSIUM: Stem cell niche and postnatal muscle growth1,2

Abstract: Stem cell niche plays a critical role in regulating the behavior and function of adult stem cells that underlie tissue growth, maintenance, and regeneration. In the skeletal muscle, stem cells, called satellite cells, contribute to postnatal muscle growth and hypertrophy, and thus, meat production in agricultural animals. Satellite cells are located adjacent to mature muscle fibers underneath a sheath of basal lamina. Microenvironmental signals from extracellular matrix mediated by the basal lamina and from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 145 publications
1
17
0
1
Order By: Relevance
“…In transgenic mice, skeletal muscle DLK1 is overexpressed, caused hypertrophy traits and affected muscle growth; similarly, a double muscled trait was caused in sheep (Davis et al, 2004;Magee et al, 2011;Bi and Kuang, 2012). In the present study, DLK1 expression was higher in the longissimus dorsi of males than in females at different growth stages after birth.…”
Section: Discussionsupporting
confidence: 54%
“…In transgenic mice, skeletal muscle DLK1 is overexpressed, caused hypertrophy traits and affected muscle growth; similarly, a double muscled trait was caused in sheep (Davis et al, 2004;Magee et al, 2011;Bi and Kuang, 2012). In the present study, DLK1 expression was higher in the longissimus dorsi of males than in females at different growth stages after birth.…”
Section: Discussionsupporting
confidence: 54%
“…If the point mutation occurs in both the paternal and maternal alleles, it causes no change in DLK1 protein expression (4), which is consistent with the mode of inheritance of the CLPG phenotype. It has been demonstrated that DLK1 protein expression is essential for determining muscle mass (20)(21)(22)(23)(24). Thus, a hypothesis predicting that maternal noncoding RNA might act as a negative regulator of DLK1 expression has been put forth; however, this hypothesis lacks evidence (25).…”
mentioning
confidence: 99%
“…These cells may not exclusively provide a pool of preadipocytes capable of differentiation to adipocytes upon stimulation. They can differentiate into other cell types in other tissues and under different conditions (Bi & Kuang, 2012;Ferrón et al, 2011; Yanai et al, 2010). Bi and Kuang (2012) assumed that DLK1 mediates the interaction between adipogenic and myogenic progenitor cells and regulates their differentiation.…”
Section: Discussionmentioning
confidence: 99%